Eventos de corrida de rua em Fortaleza-CE como comunicação de marca - Ribeiro, Andersson Teixeira (2009)
This study had the objective to verify if the events of street race transmit values to brands. Quantitative study of the transversal type, exploratory and descriptive character, developed with practicing individuals of race in the Avenue Side Sea, located in the city of Fortaleza, Ceará. The sample was composed for 153 corridors. The data had been collected by means of form during the may months the july of 2009. The analysis of the data if gave with support of software SPSS 16.0. A predominance of the masculine sex was gotten, in its majority, bachelors, working in integral period and with superior level of the school. These had 34 years on average, and the half of them gained R$4.000 to the month more than. Amongst the events, the Maratona de Revezamento Pão de Açucar was the one that had more adepts between the interviewed ones. The participation of other friends met as bigger incentive to the participation in the events of street race. Already in relation to the representation of the events for the running ones one notices that more than the half considers the participation in these races a welfare sensation. With regard to the propensity the purchases of products of the marks sponsors after to participate of these events, indicated that half of the sample would possibly buy such products. Remembering that little more than the half of the interviewed ones had related to give to attention to the brand sponsors of the events that had participated.